2022
DOI: 10.3390/ijerph20010287
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Antibiotic Use and Disposal at Household Level in Informal Settlements of Kisumu, Kenya

Abstract: The use and abuse of antibiotics are directly related to the development of drug resistance, a global public health problem. Whereas the majority of research focus is on the use and misuse of antibiotics in drug resistance development, little is known about improper disposal, as a source of contamination in the environment that includes groundwater, especially in informal settlements. This study sought to determine antibiotic use and disposal in informal settlements in Kisumu, Kenya. A random cross-sectional s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…All pseudomonad isolates had a MARI greater than 0.43, suggesting a high selective pressure in the current study environments, probably due to widespread antibiotic use and abuse, as reported in a previous study on the use and disposal of antibiotics in households in Kisumu, Kenya. 46 To prevent dissemination of MDR-pseudomonads, protecting water systems from contamination, thus incorporating the principle of one-health where environmental health translates directly to human health remains a top priority.…”
Section: Discussionmentioning
confidence: 99%
“…All pseudomonad isolates had a MARI greater than 0.43, suggesting a high selective pressure in the current study environments, probably due to widespread antibiotic use and abuse, as reported in a previous study on the use and disposal of antibiotics in households in Kisumu, Kenya. 46 To prevent dissemination of MDR-pseudomonads, protecting water systems from contamination, thus incorporating the principle of one-health where environmental health translates directly to human health remains a top priority.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that more than 80 active pharmaceutical ingredients and metabolites have been found in underground and surface water in Europe and the US [64]. In 2015 and 2018, the European Union (EU) established a watch list that included antibiotics such as amoxicillin, erythromycin, ciprofloxacin, and clarithromycin perceived to negatively affect aquatic lives and the environment in general [70]. A call to world experts and world leaders by the World Health Organization (WHO) has been made to reduce the antimicrobial pollution of our environment [71].…”
Section: Antibiotic Waste Disposal: Global Perspective and Methodsmentioning
confidence: 99%
“…Higher prevalence of infectious diseases in informal settlements is s major driver for increased antibiotic use, leading to increased demand for antibiotics due to low capacity to access information to make informed health choices particularly in developing nations [5]. Antibiotic use in the informal settlement was found to be 43%, with the majority acquiring antibiotics without a prescription for a qualified health practitioner, choosing to self-medicate, which may accelerate selection and spread of antibiotic resistant microbes [6]. Access to antibiotics in informal settlements without a prescription is easy, where the health practitioners are not necessarily qualified or are not competent [7].…”
Section: Introductionmentioning
confidence: 99%